Optimizing the Role and Increasing Knowledge of Women of Childbearing Age About Contraception at the Pratama Lena Clinic, Purwakarta, Indonesia - Zakirman, Devita (HM Publisher, 2023)
As an effort to promote family planning, the government and health workers can provide comprehensive reproductive health services, including consultations about contraception, health checks, and contraceptive installation. Contraceptive education through counseling or lectures can be effective in increasing public understanding of various contraceptive methods, their benefits, and how to use them. Counseling or lectures enable the delivery of targeted and comprehensive information to individuals or groups. This study aimed to describe contraceptive education for women of childbearing age at the Pratama Lena Clinic, Purwakarta. This study is a descriptive observational research. The research location was at the Pratama Lena Clinic, Purwakarta, Indonesia. A total of 35 respondents took part in this study. The inclusion criteria for research subjects were women aged 19-35 years and willing to take part in this research. Most respondents were aged 26-30 years (65.7%), had a senior high school education (62.9%) and used injectable contraception (45.7%). Based on pre and post-assessment evaluations, there was an increase in knowledge about contraception by 50%. The increase in knowledge obtained by participants reflects that participants are able to accept the information received through health education. In conclusion, reproductive health and contraception education programs for women of childbearing age can increase knowledge and acceptance of contraceptive use.